A case of Saturday night retinopathy following postoperative orbital compression bandaging: Diagnosis and evaluation using multimodal imaging - Rong Luan; Jinzhi Zhao; Zeying Liu; Limin Zhu; Lingyao Kong; Xiaorong Li; Tingting Lin (Photodiagnosis and Photodynamic Therapy)
We report a rare case of Saturday Night Retinopathy (SNR) following postoperative orbital compression bandaging, highlighting the value of multimodal imaging in diagnosis and management. A 24-year-old male underwent surgical repair of an inferior orbital wall fracture with an absorbable implant, followed by compression bandaging of the right eye for three days. Upon bandage removal, the patient experienced a significant drop in visual acuity (VA) from 20/20 to 20/200. Multimodal imaging, including diagnostic imaging and angiography, revealed retinal and choroidal ischemia without optic nerve compression, confirming the diagnosis of SNR. The patient received intravenous corticosteroids, which led to a gradual recovery of VA to 20/20 over several weeks. This case underscores the critical role of multimodal imaging in identifying ischemic changes and guiding timely treatment. It also highlights the risk of ischemic complications from postoperative bandaging. To our knowledge, this is the first case of SNR due to compression bandaging, emphasizing the need for cautious postoperative care and the utility of advanced imaging techniques in ophthalmology.